Observations of Pink-footed and Barnacle Geese in the Kong Oscar Fjord region of north-east Greenland, 1974 - Ferns, P N; Green, G H (Wildfowl, 1975)
Pink-footed Geese Anser brachyrhynchus bred successfully at three sites in Kong Oscar Fjord, N.E. Greenland in 1974. 26 nests were found, the average clutch size was 3.7 and 129 goslings were counted. Barnacle Geese Branta leucopsis bred successfully at all four sites visited, the average brood size was 2.8 and 272 goslings were counted. 628 adult Pinkfeet and 2,178 adult Barnacle Geese were observed, about 80% of the former species and 90% of the latter being non-breeders or breeders that failed to rear any young. The number of adults of both species showed increases over previous counts in 1961. The number of breeding pairs in the area was estimated to be 60 Pinkfeet and 110 Barnacle Geese; only Pinkfeet showed any evidence of an increased breeding population since 1963.